Branding dan Manajemen Keuangan Produk Diversifikasi Berbasis Bunga Telang pada Ibu PKK Kelurahan Rangkah Tambaksari Surabaya-SDG’s-1: Branding and Financial Management of Telang Flower Based Diversification Products in the PKK Women's Group, Rangkah Tambaksari Village, Surabaya-SDG's-1 - Ekowati, Juni; Isnalita, Isnalita; Bermawi, Bastiana; Yuwono, Mochammad; Adrianto, Muhammad Faris; Purwitasari, Neny; Ifadotunnikmah, Farida; Pratama, Adam; Ichsanto, Farhan Hanang; Setiawan, Albertus Aditya; Wahyuningsih, Etik; Rianti, Dian Ratna; Febrianti, Winanda Rizki (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Product branding and effective financial management are essential to boosting the economy of processed food production. However, PKK mothers in Rangkah Tambaksari Village, Surabaya, face challenges, including limited skills in attractive packaging techniques and financial management for calculating business profits and losses. These challenges serve as the basis for community service activities aimed at supporting the Tri Dharma Perguruan Tinggi initiative. The activities include counseling on product branding and financial management to help address these issues. The goal is to improve the quality of processed food production and its connection to human health, ultimately fostering a healthy and prosperous community. Improving the participants' skills is also expected to increase economic value, contributing to efforts to overcome poverty (aligned with the